Assessment of the application of HACCP in the preparation of blenderized feeding formula in a hospital foodservice - Cea, Ellen Estremera (2005)
An assessment of the HACCP (Hazard Analysis and Critical Control Point)Program for blenderized feeding formula in a government hospital food service was done. Data were gathered through survey, documentation analysis, actual observation and microbiological evaluation. Hospital administration extended support and showed commitment to the Program in terms of materials, equipment and facilities, and training. A well coordinated effort among different departments to promote food safety was noted. Food service staff, ages between 30 to 49 years old, had varied levels of education and over ten years of service to the institution. Majority have undergone training and were knowledgeable about the food safety procedures, were familiar with HACCP and perceived this as the present food safety program of the hospital. Majority regarded food safety procedures as very important in their food service operation, which aims to provide safe food. Findings showed non-conformance with some aspects of GMP (Good Manufacturing Practices). Low microbial contamination during formula preparation was attributed to the observance of standard food safety procedures. Nursing staff, ages 20 to 29 years, had tertiary education and only 1 to 2 years of service in the hospital. They were knowledgeable about the food safety procedures and its importance in providing safe food. Standard nursing care procedures were practiced in formula feeding, although food safety practices in handling the formula were not regularly observed, as evidenced by higher microbial contamination during formula administration. Findings revealed that the hospital has established food safety procedures in blenderized feeding preparation and administration to support the application of HACCP system. Principles of HACCP system were noted in the different processes of formula preparation and administration. Based on the evaluation of food safety procedures in formula preparation and administration, a HACCP model for blenderized feeding was developed. A very high level of compliance to GMP is recommended prior to the application of the HACCP Program.